2020
DOI: 10.3389/fmicb.2020.575377
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency Testing of Metagenomics-Based Detection of Food-Borne Pathogens Using a Complex Artificial Sequencing Dataset

Abstract: Metagenomics-based high-throughput sequencing (HTS) enables comprehensive detection of all species comprised in a sample with a single assay and is becoming a standard method for outbreak investigation. However, unlike real-time PCR or serological assays, HTS datasets generated for pathogen detection do not easily provide yes/no answers. Rather, results of the taxonomic read assignment need to be assessed by trained personnel to gain information thereof. Proficiency tests are important instruments of validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Similarly, reads classifying as pigeon picornavirus mapped to a conserved picornaviral sequence (RdRp motif) and thus most likely reflect RdRp sequences from Sicinivirus . The validation of the NDV detection based on only 3 reads and the invalidation of relatively high normalized “non-gamma” coronaviral read counts as conserved coronaviral domains illustrate the critical importance of expert interpretation and follow-up of metagenomic results as was also highlighted in a recent proficiency study [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reads classifying as pigeon picornavirus mapped to a conserved picornaviral sequence (RdRp motif) and thus most likely reflect RdRp sequences from Sicinivirus . The validation of the NDV detection based on only 3 reads and the invalidation of relatively high normalized “non-gamma” coronaviral read counts as conserved coronaviral domains illustrate the critical importance of expert interpretation and follow-up of metagenomic results as was also highlighted in a recent proficiency study [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to detect species pertinent to risk assessment, it is indispensable to target pathogens, thence effortlessly removing trivial data for risk assessment. Doing this will no doubt minimize one of the major challenges of metagenomic studies, the difficulties associated with data analysis 96 .…”
Section: Application Of Whole Genome Sequencing and Metagenomics In O...mentioning
confidence: 99%
“…Most virus specific pipelines rely on k-mer frequency classification, sometimes with protein alignment based verification (Zhao et al, 2013 ; Roux et al, 2015 ; Ren et al, 2017 ; Alam and Chowdhury, 2020 ; Nayfach et al, 2020 ). However as Höper et al ( 2020 ) demonstrated bioinformatic pipelines require further harmonization and standardization for diagnostic application. A comprehensive review on bioinformatic processing of viral sequencing data is required and the current pandemic (COVID-19) has placed our knowledge gaps and ability to interpret sequence data, front, and center.…”
Section: Future Directionsmentioning
confidence: 99%